The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/mi11060546
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of an Aluminum Underlayer in the Biocompatibility and Mechanical Integrity of Vertically Aligned Carbon Nanotubes for Interfacing with Retinal Neurons

Abstract: Retinal implant devices are becoming an increasingly realizable way to improve the vision of patients blinded by photoreceptor degeneration. As an electrode material that can improve restored visual acuity, carbon nanotubes (CNTs) excel due to their nanoscale topography, flexibility, surface chemistry, and double-layer capacitance. If vertically aligned carbon nanotubes (VACNTs) are biocompatible with retinal neurons and mechanically robust, they can further improve visual acuity—most notably in subretinal imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
(76 reference statements)
1
9
0
Order By: Relevance
“…VACNT flexibility also likely plays a role since neurons are known to readily adhere to and grow processes on softer substrates [ 94 , 95 ]. Although it has been suggested that CNT functionalization is necessary for biocompatibility, our observations support previous results demonstrating that appropriate degrees of texture and flexibility of pristine VACNTs are sufficient for neural network survival [ 83 ], which in turn favors recording and stimulation [ 96 ]. The increased process density at our electrode edges is also consistent with previous work showing that neurons respond to topographical cues [ 38 , 97 , 98 ] for a range of feature sizes [ 99 101 ] and in particular that they align with the direction of minimum surface curvature, so favoring paths that minimize process bending [ 102 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…VACNT flexibility also likely plays a role since neurons are known to readily adhere to and grow processes on softer substrates [ 94 , 95 ]. Although it has been suggested that CNT functionalization is necessary for biocompatibility, our observations support previous results demonstrating that appropriate degrees of texture and flexibility of pristine VACNTs are sufficient for neural network survival [ 83 ], which in turn favors recording and stimulation [ 96 ]. The increased process density at our electrode edges is also consistent with previous work showing that neurons respond to topographical cues [ 38 , 97 , 98 ] for a range of feature sizes [ 99 101 ] and in particular that they align with the direction of minimum surface curvature, so favoring paths that minimize process bending [ 102 ].…”
Section: Discussionsupporting
confidence: 88%
“…In addition to providing textured regions with intricate lateral shapes, the high aspect ratios of the VACNTs could aid penetration into neural tissue such as the retina [ 82 ]. Building on a broad range of CNT compatibility studies (including in vitro [ 83 ], rat in vivo [ 84 ], and human ECG tests [ 85 ]), we focus on in vitro experiments due to the controlled environment in which fluorescence and electron microscopy can be used to examine cell behavior and cell-electrode interactions as they evolve over periods of up to 17 days in vitro (DIV). Previous studies demonstrating that electrically-biased CNT electrodes stimulate neurons effectively [ 86 88 ] and even boost their signal transmission [ 77 , 78 , 89 , 90 ] indicate that our fundamental studies of cell arrangement have large potential for translation to future electrical measurements and applications.…”
Section: Introductionmentioning
confidence: 99%
“…The substrates were modified by immobilizing laminin following protocols explained elsewhere to increase the surface biocompatibility prior to the cell cultures [3]. The substrates were then covered with a suspension of dissociated mouse retinal cells, obtained following ethical approval and protocols previously described elsewhere [4]. Neuronal and glial cells were identified using immunofluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that neurons prefer to adhere to CNT structures [ 10 , 13 , 14 ] rather than to the smooth surfaces of traditional sensors [ 10 ]. Thin film CNT FETs have been employed for a range of electronic sensing applications, from hormone detection to the detection of molecular dynamics [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%